The role of trade policy in promoting sustainable agriculture - Fredrik Erixon; Philipp Lamprecht (European Centre for International Political Economy (ECIPE), 2020)
There is now a long history of countries improving sustainability standards in most parts of the economy while at the same time pursuing the ambitions of rules-based international trade and economic integration with other countries. It is not surprising that countries at the vanguard of sustainability also tend to be the countries that are most open to trade. This Report looks closer at the interplay between the formulation of domestic standards and provisions in Free Trade Agreements that either acknowledge domestic standards or establish standards in a direct way. This interplay is crucial for two reasons: first to establish market access arrangements that help to promote sustainability standards, second to provide the policy basis to make standards and possible market access restrictions conducive to basic trade rules.
Keywords: 330; Freihandelsabkommen; Umweltstandard; Ökologischer Landbau; Ernährungsindustrie; Welt; Norwegen